Mental disorders in judicial workers: analysis of sickness absence in a cohort study - Melo, Bruna Ferreira; Santos, Kionna Oliveira Bernardes; Fernandes, Rita de Cássia Pereira; Lima, Verônica Maria Cadena de; Stock, Susan (Revista de Saúde Pública, 2023)
OBJECTIVE: To analyze risk factors for sickness absence due to mental disorders among judicial workers in Bahia, Brazil. METHODS: Retrospective cohort with follow-up from 2011 to 2016 with 2,660 workers of a judicial sector in Bahia, Brazil. The main outcome measures were survival curves estimated for the independent variables using the Kaplan-Meier product limit estimator and risk factors for the first episode of sickness absence calculated based on the Cox regression model. RESULTS: The survival estimate of the population of this study for the event was 0.90 and from the Cox model the risk factors for the first episode of sickness absence due to mental disorders were: female (HR = 1.81), occupation of magistrate (HR = 1.80), and age over 30 years old (HR = 1.84). In addition, the risk for new cases of sickness absence among women reached 4.0 times the risk for men, in 2015. The estimated relative risks of sickness absence and the observed survival reduction behavior over time add information to the literature on sociodemographic and occupational factors associated with sickness absence due to mental disorders in the public sector. CONCLUSION: These results highlight the need for further research to more precisely identify vulnerable groups at risk of preventable mental health-related sickness absence in the workplace, better identify the workplace organizational factors that contribute to these disorders as well as studies on the effectiveness of workplace interventions to improve mental health among judicial and other public sectors workers.